Prevalence of dyspepsia and associated sociodemographic factors - Oliveira, Sandro Schreiber de; Santos, Iná da Silva dos; Silva, José Francisco Pereira da; Machado, Eduardo Coelho (Revista de Saúde Pública, 2006)
OBJECTIVE: To assess prevalence of dyspepsia and distribution of dyspepsia and frequent dyspepsia in subgroups of adults (20 years and older) according to their demographic and socioeconomic characteristics. METHODS: A cross-sectional population-based study was carried out comprising 3,934 subjects living in Pelotas, Southern Brazil, from October 1999 to January 2000. Data was collected through household interviews. Dyspepsia was defined as epigastric pain or disconfort associated or not with nausea in the previous year, according to Rome I and Rome II criteria. Frequent dyspepsia was defined as more than six dyspepsia episodes in the previous year and/or nausea, at least once a month. These outcomes were analyzed according to age, gender, skin color, educational level, per capita income and marital status. Data analysis was carried out through Pearson Chi-square test for categorical variables and linear trend test, when applicable. RESULTS: The prevalence of dyspepsia was 44.4% and frequent dyspepsia, 27.4%. The prevalences of reflux-like, ulcer-like, dysmotility-like and unspecific dyspepsia subtypes were 19.4%, 6.3%, 13.9%, and 16.6%, respectively. The prevalences of these subtypes of frequent dyspepsia were 14.7%, 4.9%, 11.2% and 6.8%, respectively. Prevalences among women were 50% higher. Low-income young people seemed to be more affected by dyspeptic symptoms. The analysis according to Rome II criteria showed prevalences of 15.9% and 7.5% for dyspepsia and frequent dyspepsia, respectively. CONCLUSIONS: Dyspepsia and frequent dyspepsia were prevalent problems in the studied population. Most people could be classified in more than one subgroup of dyspepsia.